PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW PADA MATERI KETERGANTUNGAN ANTAR RUANG DAN PENGARUHNYA TERHADAP KESEJAHTERAAN MASYARAKAT DI SMP NEGERI 8 KOTA BOGOR - Ni Made Suratini (Universitas Pakuan, 2021)
IMPROVING STUDENT LEARNING OUTCOMES USING THE JIGSAW LEARNING MODEL ON THE MATERIAL DEPENDENCE BETWEEN SPACES AND ITS EFFECT ON THE WELFARE OF THE COMMUNITY IN JUNIOR HIGH SCHOOL (SMP NEGERI 8 KOTA BOGOR)The low learning outcomes of students in Social Science subjects, especially the material about interdependence between spaces and their influence on the welfare of society in grade 9C of SMP Negeri 8 Bogor, is the problem behind this research. In the learning process, students lack concentration and are motivated so that they have difficulty in receiving the material presented. This study aims to determine the increase in student learning outcomes about interdependence between spaces and their effect on people's welfare after using the Jigsaw learning model; describe the process of improving student learning outcomes about the interdependence between spaces and their effect on the welfare of society after using the Jigsaw learning model; This type of research is Classroom Action Research with two cycles where in one cycle consists of two meetings. The results showed that by using the Jigsaw learning model there was an increase in student learning outcomes. This can be seen from the completeness of learning outcomes. After using the Jigsaw learning model in the first cycle, the completeness of learning outcomes achieved was 84.85% or as many as 28 people. In the second cycle of learning using the Jigsaw learning model has reached / exceeded completeness because 100% of students have scores above the KKM. Based on the results of these studies, it can be concluded that the use of the Jigsaw learning model can improve the learning outcomes of students in grade 9C at SMP Negeri 8 Bogor in social studies subjects, especially on the material about interdependence between spaces and their influence on people's welfare.